Dietary Klebsormidium sp. Supplementation Improves Growth Performance, Antioxidant and Anti-Inflammatory Status, Metabolism, and Mid-Intestine Morphology of Litopenaeus Vannamei - Fang, HaoHang; Zhuang, ZhenXiao; Huang, LuoDong; Zhao, Wei; Niu, Jin (Frontiers in Nutrition, 2022)
Filamentous microalga Klebsormidium sp. has the huge potential to become a nature and healthy additive in aquatic diet since it contains various bioactive nutrients, like linoleic acid (LA), carotenoids and chlorophyll. Therefore, an 8-weeks feeding experiment was performed to evaluate the effects of dietary Klebsormidium sp. on the growth performance, antioxidant, anti-inflammatory, metabolism and mid-intestine morphology of Litopenaeus vannamei. Two isonitrogen and isolipids diets supplemented with/without 5% Klebsormidium sp. were formulated respectively. Results showed that L. vannamei fed with Klebsormidium sp. obtained the better growth performance and feed utilization by optimizing mid-intestine morphology and improving the carbohydrate metabolism. In addition, Klebsormidium sp. also enhanced the antioxidant capacity of L. vannamei by downregulating antioxidant parameters (hepatopancreas T-SOD, hepatopancreas GSH-PX, hemolymph T-SOD, hemolymph MDA) and the expression levels of antioxidant genes (GSH-PX and CAT). Furthermore, the dietary Klebsormidium sp. supplementations significantly improved hepatopancreas health by down-regulating the expression levels of pro-inflammatory related genes (Relish and Rho). In conclusion, the dose of 5% Klebsormidium sp. was recommended for the daily diet of L. vannamei, which could improve the growth performance, antioxidant, anti-inflammatory, carbohydrate metabolism and mid-intestine morphology of shrimp.